Involvement of F-BOX proteins in progression and development of human malignancies. (February 2016) - Uddin, Shahab; Bhat, Ajaz A.; Krishnankutty, Roopesh; Mir, Fayaz; Kulinski, Michal; Mohammad, Ramzi M.
Abstract: The Ubiquitin Proteasome System (UPS) is a core regulator with various protein components (ubiquitin-activating E1 enzymes, ubiquitin-conjugating E2 enzymes, ubiquitin-protein E3 ligases, and the 26S proteasome) which work together in a coordinated fashion to ensure the appropriate and efficient proteolysis of target substrates. E3 ubiquitin ligases are essential components of the UPS machinery, working with E1 and E2 enzymes to bind substrates and assist the transport of ubiquitin molecules onto the target protein. As the UPS controls the degradation of several oncogenes and tumor suppressors, dysregulation of this pathway leads to several human malignancies. A major category of E3 Ub ligases, the SCF (Skp–Cullin–F-box) complex, is composed of four principal components: Skp1, Cul1/Cdc53, Roc1/Rbx1/Hrt1, and an F-box protein (FBP). FBPs are the substrate recognition components of SCF complexes and function as adaptors that bring substrates into physical proximity with the rest of the SCF. Besides acting as a component of SCF complexes, FBPs are involved in DNA replication, transcription, cell differentiation and cell death. This review will highlight the recent literature on three well characterized FBPs SKP2, Fbw7, and beta-TRCP. In particular, we will focus on the involvement of these deregulated FBPs in the progression and development of various human cancers. We will also highlight some novel substrates recently identified for these FBPs.